2010
DOI: 10.1348/096317909x479394
|View full text |Cite
|
Sign up to set email alerts
|

Extending the job design perspective on individual innovation: Exploring the effect of group reflexivity

Abstract: Extending previous research on group reflexivity as a group level predictor of individual innovation, we examined group reflexivity as a possible moderator of the effect of job control and task complexity on individual innovation. We obtained data on job and group characteristics from 135 members of software development teams; line managers provided ratings on individual innovation. Data were analysed using hierarchical linear modelling. Results lend further support to a positive effect of job design on indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…Research has indicated that HRM practices can have different effects on idea generation and on idea implementation. Our analysis has shown, for example, that task complexity has a negative effect on creativity and idea generation, but a positive effect on idea implementation (Ohly et al, 2006;Urbach et al, 2010). A more recent study (Veenendaal and Bondarouk, 2015) shows that perceptions of training and development have a significant effect on idea generation but not on idea promotion and idea implementation.…”
Section: Limitationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Research has indicated that HRM practices can have different effects on idea generation and on idea implementation. Our analysis has shown, for example, that task complexity has a negative effect on creativity and idea generation, but a positive effect on idea implementation (Ohly et al, 2006;Urbach et al, 2010). A more recent study (Veenendaal and Bondarouk, 2015) shows that perceptions of training and development have a significant effect on idea generation but not on idea promotion and idea implementation.…”
Section: Limitationsmentioning
confidence: 60%
“…Tasks that are particularly routine can help preserve important cognitive and time resources that are necessary to generate and implement useful ideas (Ohly et al, 2006). Job complexity has been shown not to have a significant impact on creativity (Ohly et al, 2006) or on idea generation (Urbach et al, 2010), but to significantly affect implementation (Ohly et al, 2006;Urbach et al, 2010). Ohly et al (2006) explain these findings with the suggestion that employees who frequently carry out particular tasks can use their spared cognitive and time resources to generate and implement new and useful ideas.…”
Section: Hrm and Iwbmentioning
confidence: 99%
“…For example, having diverse or dissenting opinions in a team contributes to team innovation provided the team shows a high level of reflexivity (De Dreu, ), and a similar effect has been found for team knowledge diversity (Fay et al., ). Furthermore, higher team reflexivity helps to make more effective use of job control in the course of making innovative contributions (Urbach, Fay & Goral, ).…”
Section: Constraining or Facilitating Context: The Role Of Hrm For Thmentioning
confidence: 99%
“…One core aspect of self-directed teams is the autonomy they have over work operations (Morgeson et al, 2006). Autonomy leads to a sense of responsibility and increases intrinsic motivation, which in turn is associated with conception and implementation of new ideas (Amabile, 1996;Urbach, Fay & Goral, 2010). Furthermore, teamwork may also benefit creativity because individuals tend to experience positive feelings through working in teams (relative to more traditional working arrangements; Wall et al, 1986; see also the metaanalysis by Richter, Dawson & West, 2011).…”
Section: The Use Of Teamwork and Organizational Innovationmentioning
confidence: 99%
“…Reflexive teams benefit from distinct cognitions; they encourage each member to attach importance to their own viewpoint and promote proactive thinking instead of settling for habitual thoughts and routine behaviours (Schippers, Homan, & Knippenberg, ; Urbach, Fay, & Goral, ). This is necessary for generating novel ideas.…”
Section: Introductionmentioning
confidence: 99%